Modular Programming of Functions for Turbo Product Codes on FPGA - Sandoval Ruiz, Cecilia Esperanza (Revista Técnica da Faculdade de Engenharia da de Zulia)
This paper present a review of the concepts turbo product codes, with the aim of designing an alternative based on the high degree of parallelism available in the reconfigurable hardware devices such as the FPGA, using these devices arrangements composed by field programmable; for designing functional modules such encoders. The selected modules have been described in language descriptor hardware, synthesized and simulated, using the design tool Xilinx ISE 9.2i, which was conducted with the programming of components, and sets out the findings on the basis of the alternatives raised. Â Â